CONCEPTIONS OF RATIO AND PROPORTIONS AMONG YEAR FIVE PUPILS: CASE STUDY - Vani a/p Perumal,; Sharifah Norul Akmar Syed Zamri, (MOJES: Malaysian Online Journal of Educational Sciences, 2022)
Ratios and proportions are new topics in the primary curriculum. Previous research shows that Year Five pupils have difficulty in learning ratio and proportion. This study aims to identify the conceptions of ratio and proportion of seven year five pupils. It is based on radical constructivism using qualitative case study. Data was collected through a clinical interview technique. The data collected include the mental image of the ratio and proportion, representation of ratio and proportion, and the meaning of ratio and proportion. The cross-case analysis between the samples showed that the year five pupils could construct knowledge that make sense and gave the meaning of ratio as comparison of quantities, part to part comparisons, useful in daily activities, belongings, cooking, and parts of the body. Meanwhile, proportions are meaningful to them as part to whole comparisons and as two equal ratios that are related multiplicatively. This study gives implications to a few aspects mainly to the theory, teaching and learning practice, curriculum, textbook developers, and implication for future research.